Development of a Microservices-Based Geographic Information System for Mapping Flora and Fauna in Kutai National Park - Rasni Alex; Nur Maulida Sari; Aulia Khoirunnita; Indah Fitri Astuti; Dedy Cahyadi; Awang Kridalaksana; Ida Maratul Khamidah (JURNAL AGRIMENT, 2025)
Kutai National Park serves as a vital habitat for diverse flora and fauna, yet the park faces challenges in achieving comprehensive and efficient mapping of its biodiversity. In alignment with the 2019–2029 Long-Term Management Plan, which prioritizes completing a robust mapping system, this study proposes the development of a Geographic Information System (GIS) based on a microservices architecture. The system aims to streamline data management and support area conservation efforts. Utilizing the Extreme Programming methodology, the project leverages React JS for the web interface, React Native for mobile applications, and MongoDB for database management. System testing incorporates Postman for microservices, Selenium for web applications, and Black-Box testing for mobile apps. Feasibility evaluations use Equivalence Partitioning and the Mean Opinion Score (MOS) method, reflecting high acceptance among staff (71% Strongly Agree, 29% Agree) and visitors (47.9% Strongly Agree, 43% Agree, 3.8% Neutral). The results demonstrate the system's potential to enhance biodiversity management while fostering stakeholder engagement in conservation initiatives